Penerapan Metode Pembelajaran Mind Mapping Untuk Meningkatkan Keterampilan Menulis Siswa Kelas V SD YPPI-II Surabaya - Musrini, ; Imam Rofiki, ; Ahnan Alex, ; Dwi Ema Hartiwi, (Pendidikan Sekolah Dasar, 2009)
This Classroom Action Research is based by the existence of the problems at 5th. Grade students of SD YPPI-II Surabaya, namely low skill level of the students in writing. Subsequently, the objective of this research is to find out whether the Mind Mapping learning method can be used to help the 5th Grade students improve their sill in writing and to find out the obstacles encountered in the implementation Mind Mapping learning method. This research is using the sequences of planning, research action implementation, observation and reflection for every cycle. In planning phase, some scenes, such as learning, students worksheet, assessment tools, and observation instruments are prepared. In research action phase, the observation towards learning management, and the assessment towards the concept understanding of Mind Mapping, as well as the writing results are conducted. The reflection is conducted by analyzing the observed data and the assessment result, by using class completion percentage of 85% as the standard of the result success. This research is conducted by 2 cycle rounds of research. The research results show that the Mind Mapping learning method has succeeded in improving the students skills in writing orderly. Some students obtain low scores because of their inability in mastering the diction choice and spelling use in writing. In addition, some students think that the time allocation provided to do students worksheet is not accordance with the difficulty level of the assignment provided. Based on the reflection of the first cycle and the improvement conducted at the second cycle, it can be inferred that the key factor that can be the obstacle to implement the Mind Mapping learning method in class is the teacher herself that has not mastered some basic skills of teaching and basic skills of learning management.